Design, molecular docking analysis of an anti-inflammatory drug, computational analysis and intermolecular interactions energy studies of 1-benzothiophene-2-carboxylic acid. (October 2020) - Sagaama, Abir; Issaoui, Noureddine
Graphical abstract: Highlights: Structural analysis of 2BT acid was performed using DFT calculation. Pharmaceutical properties were discovered by molecular docking analysis. The FT-IR and FT-Raman were reported and compared with theoretical ones. AIM, Hirshfeld surface analysis demonstrates the different non covalent interactions. Abstract: In this paper, theoretical study on molecular geometry, vibrational, pharmaceutical and electronic properties of the monomeric and dimeric structures of 1-benzothiophene-2-carboxylic acid (2BT) were carried out using B3LYP hybrid functional with 6-311++G(d, p) as basis set. The structural study show that the stability of 2BT crystalline structure arising from O-H…O, C-H…O as well as S-H…O hydrogen bonding interactions. Vibrational analysis, for monomer and dimer species, show a good compatibility between experimental and theoretical frequencies. Then, the 1H and 13C NMR chemical shifts were calculated using Gauge Independent Atomic Orbital (GIAO) technical. In addition, the UV-Vis spectrum was simulated in gas phase and in water throughout TD-DFT calculation. The electronic transitions were identified based on HOM-LUMO energies. However, donor-acceptor interactions and charge delocalization has been studied via natural bond orbital (NBO). The nucleophilic and electrophilic site localization is identified by molecular electrostatic potential. Hirshfeld surface analysis has been discussed based on color code demonstrating the various non covalent interactions. Besides, molecular docking analysis was reported to evince the pharmaceutical properties of the studied molecule.